SACrA score to predict the initiation of renal replacement therapy in critically ill patients: a single-center retrospective study - Ginga Suzuki; Saria Nishioka; Toshimitsu Kobori; Yuka Masuyama; Saki Yamamoto; Hibiki Serizawa; Yoshimi Nakamichi; Mitsuru Honda (Renal Failure, 2024)
Background Acute kidney injury (AKI) is a prevalent complication in critically ill patients that affects the timing of renal replacement therapy (RRT) initiation. This study aimed to develop and validate the SACrA score for predicting non-emergent initiations (BUN ≥112 mg/dL or oliguria for >72 h) of RRT in critically ill patients.Methods We conducted a retrospective cohort study using data from two cohorts. The derivation cohort included patients admitted to the ICU between November 2021 and December 2023, whereas the validation cohort included patients admitted between September 2019 and October 2021. The primary outcome was non-emergent RRT initiation. The multivariate logistic regression with stepwise selection based on the Akaike information criterion finalized the model, including the variables, such as sex, albumin (Alb), creatinine (Cr), and APACHE II score (SACrA).Results The derivation and validation cohorts comprised 470 and 476 patients, respectively. The SACrA score showed a strong predictive performance for non-emergent RRT initiation in both the cohorts. Cohort 1 had an ROC–AUC of 0.971, with a calibration slope of 0.982 and an intercept of 0.009, whereas cohort 2 had an ROC–AUC of 0.918, with a calibration slope of 0.988 and an intercept of 0.004.Conclusions The SACrA score is a robust tool for predicting non-emergent RRT initiation in critically ill patients using readily available clinical variables. Though additional data are needed to validate the SACrA score, our analysis suggests the tool may help clinicians make informed decisions, reduce unnecessary RRT, and thereby improve patient outcomes.